Propagation model for wireless sensor networks: Review and modeling - Latifah Munirah, Kamarudin; R. Badlishah, Ahmad, Prof. Madya Dr.; Ong, Bi Ling (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.